2006
DOI: 10.1073/pnas.0608215103
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and enhanced cortical GABAergic inhibition in two mouse models of human autosomal dominant nocturnal frontal lobe epilepsy

Abstract: Selected mutations in the human ␣4 or ␤2 neuronal nicotinic acetylcholine receptor subunit genes cosegregate with a partial epilepsy syndrome known as autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE). To examine possible mechanisms underlying this inherited epilepsy, we engineered two ADNFLE mutations (Chrna4 S252F and Chrna4 ؉L264 ) in mice. Heterozygous ADNFLE mutant mice show persistent, abnormal cortical electroencephalograms with prominent delta and theta frequencies, exhibit frequent spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
205
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(216 citation statements)
references
References 31 publications
11
205
0
Order By: Relevance
“…Enhanced GABAergic inhibition has been shown to promote seizures in a transgenic murine model of frontal lobe epilepsy that is linked to a nicotinic acetylcholine receptor mutation (Klaassen et al, 2006). Neocortical seizures sustained by nicotinic activation are suppressed in these animals by GABA A receptor antagonists, suggesting that seizure onset involves phase resetting of synchronization of principal cells determined by acetylcholine-dependent synchronization of inhibitory cortical networks.…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 99%
“…Enhanced GABAergic inhibition has been shown to promote seizures in a transgenic murine model of frontal lobe epilepsy that is linked to a nicotinic acetylcholine receptor mutation (Klaassen et al, 2006). Neocortical seizures sustained by nicotinic activation are suppressed in these animals by GABA A receptor antagonists, suggesting that seizure onset involves phase resetting of synchronization of principal cells determined by acetylcholine-dependent synchronization of inhibitory cortical networks.…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 99%
“…Furthermore, we show that activating ␣4* nAChRs in vivo by bath application or direct micro-injection of ␣4* nAChR agonist into layer 4 depressed whisker-evoked responses by 30 -50% in control mice, similar to that seen after 3-7 d of whisker deprivation. Indeed, several electrophysiological studies using both human and rodent cortical tissue have shown that ␣4* nAChR activation rapidly depolarizes cortical interneurons, that can be blocked by the ␣4* nAChR antagonist DH␤E (Xiang et al, 1998;Porter et al, 1999;Alkondon et al, 2000;Christophe et al, 2002;Klaassen et al, 2006;Couey et al, 2007;Mann and Mody, 2008). Therefore one possible mechanism underlying the depression of whisker-evoked responses is that ␣4* nAChRs may be enhancing GABAergic inhibition in deprived barrel columns.…”
Section: Mechanisms Of Experience-based Cortical Depressionmentioning
confidence: 99%
“…α4-subunit S284L transgenic rats [135] show a more complete ADNFLE phenotype, with spontaneous attacks during slow-wave sleep, comprising paroxysmal arousals (frightened behavior), dystonic activity, and epileptic wandering. Notably, the pathogenic mechanisms are also different in these models: upon application of nicotine, GABAergic inhibition is increased in frontal cortex of S252F and +L264 knockin mice [133], whereas it is reduced in somatosensory cortex of S284L transgenic rats [135].…”
Section: Autosomal Dominant Nocturnal Frontal Lobe Epilepsymentioning
confidence: 99%
“…Whereas β2 mutations showed gain of function by increased sensitivity to acetylcholine or slower desensitization [125], the α2 mutation showed gain of function by increased sensitivity to acetylcholine [128]. The α4 mutations S252F and +L264 engineered in knockin mice [133] induced spontaneous seizures of various types, in some cases similar to those of the human phenotype, but no paroxysmal arousal and dystonia-like manifestations that are typical of ADNFLE; α4 subunit knockout mice showed no spontaneous seizures, but had nicotine-induced dystonic attacks [134]. α4-subunit S284L transgenic rats [135] show a more complete ADNFLE phenotype, with spontaneous attacks during slow-wave sleep, comprising paroxysmal arousals (frightened behavior), dystonic activity, and epileptic wandering.…”
Section: Autosomal Dominant Nocturnal Frontal Lobe Epilepsymentioning
confidence: 99%